2018
DOI: 10.1093/ageing/afy106
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of sarcopenia in community-dwelling older adults, an exploration of differences between studies and within definitions: a systematic review and meta-analyses

Abstract: estimates of sarcopenia prevalence vary from 9.9 to 40.4%, depending on the definition used. Significant differences in prevalence exist within definitions across populations. This lack of agreement between definitions needs to be better understood before sarcopenia can be appropriately used in a clinical context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
250
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 313 publications
(295 citation statements)
references
References 24 publications
9
250
3
4
Order By: Relevance
“…The concept of probable sarcopenia is a recent one, and we are not aware of other studies that have assessed its prevalence in community settings. We are also not aware of studies that have examined the prevalence of sarcopenia at younger ages, with a recent systematic review reporting a minimum age of 55 years across 109 prevalence studies . Finally, we are not aware of studies that have specifically examined associations between long‐term conditions and sarcopenia, although two closely related areas of investigation are the associations of multimorbidity with grip strength as a continuous variable and with other measures of physical function, as described in the succeeding texts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of probable sarcopenia is a recent one, and we are not aware of other studies that have assessed its prevalence in community settings. We are also not aware of studies that have examined the prevalence of sarcopenia at younger ages, with a recent systematic review reporting a minimum age of 55 years across 109 prevalence studies . Finally, we are not aware of studies that have specifically examined associations between long‐term conditions and sarcopenia, although two closely related areas of investigation are the associations of multimorbidity with grip strength as a continuous variable and with other measures of physical function, as described in the succeeding texts.…”
Section: Discussionmentioning
confidence: 99%
“…We are also not aware of studies that have examined the prevalence of sarcopenia at younger ages, with a recent systematic review reporting a minimum age of 55 years across 109 prevalence studies. 28 Finally, we are not aware of studies that have specifically examined associations between long-term conditions and sarcopenia, although two closely related areas of investigation are the associations of multimorbidity with grip strength as a continuous variable and with other measures of physical function, as described in the succeeding texts. Several studies have shown inverse relationships between hand grip strength and the total number of long-term conditions in older individuals.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
“…With the aging of society, interest in geriatric diseases has been increasing; in particular, interest in the prevention of and intervention for sarcopenia, which is known as an important risk factor for geriatric syndromes, has escalated [2]. Sarcopenia involves deterioration of skeletal muscle tissue with age and is one of the most important causes of functional decline and loss of independence in older adults [3], increasing the risk of functional degradation, fall, hospitalization, and mortality [4]. There is consequently a need for active prevention and management of sarcopenia in community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%
“…These differences in prevalence also exist across populations even when using the same de nition. The prevalence of sarcopenia was 63% in 249 patients in long-term care facilities in Spain, based on the rst published algorithms of the European Working Group on Sarcopenia in Older People (EWGSOP) [4]. In addition, Chinese studies showed that 19.31% of 4,500 communitydwelling individuals > 50 years old (mean age 62.4 ± 8.3 years) had sarcopenia, based on the Asian Working Group for Sarcopenia (AWGS) algorithm [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation